Control of the Metal-Insulator Transition at Complex Oxide Heterointerfaces through Visible Light - Lin, Jheng-Cyuan (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.